Digitalization – Planning - Jereb, Borut (Digitalna transformacija v logistiki in managementu oskrbovalnih verig, 2025)
E-business plays a crucial role in the modern digital environment, transforming business practices and opening new possibilities. The model of the e-business value chain is presented, encompassing supporting processes, the value chain, and technological solutions. Additionally, various e-business approaches are addressed, including e-marketing, e-documentation, e-payments, and e-customer management. The importance of information and cyber security in the contemporary business environment is emphasized. Safeguarding the digital landscape becomes crucial, with information security covering the protection of information, while cyber security addresses the protection of digital systems from cyber threats. Both disciplines are essential for maintaining trust and security in e-business. The article concludes with the presentation of IT risk management using the ISO/IEC 27005 standard.